Development of Warehouse Inventory Management System: Pembangunan Sistem Pengurusan Inventori Gudang - MOHD ARIS, MUHAMMAD ANIQ; MOHD SALIKON, MOHD ZAKI (Applied Information Technology And Computer Science, 2022)
Warehouse Inventory Management System is a web-based system developed to manage company inventory information to ensure consistent supply availability for users. The case study for this system was conducted at Syarikat Global Elite Ventures Sdn. Bhd. Existing manual systems have some drawbacks as employees need a lot of time in managing or tracking data about their stock of goods. In addition, stores still use paper to store their sales reports and cause a higher percentage of data loss. Employee error in storing any data is also a major factor that will cause data duplication to occur. Therefore, an inventory system was developed to overcome this problem. After analyzing several existing systems, these systems can be computerized to improve the efficiency of goods flow and be easier to manage. The system was developed based on the Waterfall model because it is easy to practice. Next, the system program code is written using Notepad ++ software. While Xampp and Mysql as servers and system databases. The system has several function modules such as registration, login, product management, invoice management, goods receipt management and sms notification. At the end of this project, a Warehouse Inventory Management System will be produced. Work such as recording data becomes more efficient and no longer needs to use files, paper and can also save space. Furthermore, it can save time in managing inventory in the warehouse where the clerk or manager can easily access all the products in one place.